Golden Eagles in the United States of America: Threats and the Federal Response to Potential Impacts from Renewable-Energy Development - Jill A. Shaffer (Пернатые хищники и их охрана)
Golden Eagles (Aquila chrysaetos) have a Holarctic distribution. The subspecies A. ch. сanadensis inhabits North America, where it encounters the same anthropogenic threats as other eagle species worldwide, including electrocution on powerlines, shooting, collisions with vehicles, and poisoning by lead and rodenticides. A more recent threat is mortality from collisions with wind turbine blades. For the 11 States that are west of the 100th meridian and that represent most of the species’ year-round range within the coterminous United States of America (USA), over 600 individuals per year die from collisions with vehicles, wind-turbine blades, electrical power lines, and trains. Federal laws, policies, and guidelines aim to protect the Golden Eagle from the increasing threat of turbine mortality. Two Federal laws–the Migratory Bird Treaty Act and the Bald and Golden Eagle Protection Act–will be reviewed.